Reconstructing the Image of Teacher in Lesson Study - Servan-Núñez, María José; Rodriguez-Robles, Cristina (My University, 2019)
This paper presents the results of research on Lesson Study's potential to reconstruct student teachers' practical knowledge. It focuses specifically on a Lesson Study implemented as part of the subjects Practicum III and Final Dissertation, which are imparted in year four of the Degree in Infant Education at Málaga University. The work is based on qualitative research that is developed through a case study. The case selected was a group of six students, one of which was chosen for further follow-up. The Lesson Study comprises practice over the course of four months, carried out in schools as part of the Practicum III. Here the first six phases are developed: 1) Define the problem; 2) Design the experimental lesson; 3) Develop the first experimental lesson; 4) Analyse; 5) Redesign; 6) Develop the second experimental lesson and the Final Dissertation, which makes up phase seven (analysis and presentation in an expanded context). The information collection strategies we used to investigate the chosen case were observation, interview, documentary review and the researchers' diary. This research has shown Lesson Study's potential to reconstruct students' image of teaching throughout the different phases thanks to two key processes: theorisation of practice and experimentation of theory. First phase, determining the focus for the proposal: based on teachers' learning needs, allowing us to identify the image of teaching we are starting off from. Second phase, designing the proposal: we believe cooperative reflection on teachers' responses to hypothetical situations is particularly relevant, since it allows students to start to cooperatively question their own practical knowledge. The first signs of the reconstruction of the image of teaching can be seen in the proposal redesign phase between the two experimental lessons. This is the point at which the group perceives that their beliefs, fears or outlooks contrast with their experience.
Keywords: Docentes -- Formación; Lesson Study; Desarrollo profesional docente; Formación inicial de docentes; Conocimiento práctico docente